Exploring enablers of sexually transmitted infections among illegal gold miners in the midlands region of Zimbabwe - Nyashanu, Mathew; Chireshe, Rumbidzai; Jidong, Dung Ezekiel; Nyashanu, Wendy; Ekpenyong, Mandu Stephen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Sub-Saharan Africa faces by far the highest rate of HIV and other Sexually Transmitted Infections (STIs). Illegal mineworkers are considered at risk for HIV and sexually transmitted infections (STIs). Men are generally not receptive to health promotion messages. Methods: This study explored the enablers of sexually transmitted infections. The study utilized a qualitative approach. A total of 40 participants were recruited. Semi structured interviews were used to collect data. A thematic approach was used to analyze the data. Zimbabwe, like any other country in the sub-Saharan region of Africa, has been affected by the epidemic of HIV/AIDS and other STIs, because of poor sexual health education. Results: The study found that the enablers of STIs included poor sexual health knowledge, substance misuse, prolonged stay from family, stigma, lack of entertainment, cultural status, and poor sexual health services. Conclusions: STIs among illegal gold miners is a public health concern that needs urgent attention in many developing countries.